Gambaran Dermal-Epidermal Junction Pada Bullous Pemphigoid Dan Epidermolysis Bullosa Acquisita - Budiman, Caroline; Devi, Mutia; Thaha, HM Athuf (Medicinus, 2017)
Epidermis and dermis of the skin attach each other because of the role of a structure which is called dermal-epidermal junction. The dermal-epidermal junction can be divided into three distinct zones named hemidesmosome-keratin intermediate filament complex, basement membrane, and anchoring fibril. Each part of the distinct zone has significant components for the integrity of the skin. Bullous pemphigoid is an autoimmune disorder caused by autoantibody against a 180-kDa molecule now called Bullous Pemphigoid Antigen 2 (BPAG2) or type XVII collagen within basement membrane. To date, the slot deposit 5000 patophysiology and the components of dermal-epidermal junction that induce the blister formation remain unclear. Epidermolysis bullosa acquisita is an autoimmune disease with sub-epidermal blistering associated with autoimmunity to the collagen within anchoring fibrils. The pathophysiology and etiology””again””remain unknown.